Effect of Proteinuria Before Lenvatinib Administration on Treatment Response After Atezolizumab Bevacizumab Combination Therapy - Hironori Ochi; Masayuki Kurosaki; Takaaki Tanaka; Nobuharu Tamaki; Kaoru Tsuchiya; Yutaka Yasui; Hiroyuki Marusawa; Toshifumi Tada; Shinichiro Nakamura; Takehiro Akahane; Eisuke Okamoto; Haruhiko Kobashi; et al. (JGH Open)
ABSTRACT Aim We investigated the impact of proteinuria on the therapeutic effect before lenvatinib administration as second‐line treatment after atezolizumab‐bevacizumab. Methods We examined 64 patients who were administered lenvatinib as second‐line treatment after discontinuation of atezolizumab and bevacizumab. Proteinuria assessed before lenvatinib administration was considered severe if the qualitative value test (QV) was 3+ or the urine protein/creatinine ratio (UPCR) was ≥ 2.0 (group A, n = 13) and non‐severe if the UPCR was < 2.0 or the QV was ≤ 2+ (group B, n = 51). Results In the entire cohort, the modified albumin–bilirubin grades were grades 1, 2a, 2b, and 3 in 12, 21, 26, and 5 patients, respectively. Regarding the Barcelona Clinic of Liver Cancer stage, 2, 22, and 40 patients had stages A, B, and C, respectively. The objective response rate (ORR) was 14.0% and the disease control rate (DCR) was 59.3%. The median survival time and progression free survival after administration of lenvatinib was 14.8 (95% confidence interval [CI], 11.3–18.4) and 5.5 (95% CI, 3.6–7.5) months, respectively. The ORR and DCR were 0% and 38.4% for group A (n = 13) and 17.6% and 64.7% for group B (n = 51), respectively. The median time to treatment failure was 2.2 months in group A and 4.2 months in group B (p = 0.120). Conclusions Severe proteinuria before lenvatinib as a second‐line therapy after atezolizumab‐bevacizumab treatment may affect the duration of lenvatinib administration and treatment efficacy.